2006
DOI: 10.1897/05-585r.1
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase response in native birds exposed to fenitrothion during locust control operations in eastern Australia

Abstract: Huge aggregations of flightless locust nymphs pose a serious threat to agriculture when they reach plague proportions but provide a very visible and nutritious resource for native birds. Locust outbreaks occur in spring and summer months in semiarid regions of Australia. Fenitrothion, an organophosphate pesticide, is sprayed aerially to control locust plagues. To evaluate fenitrothion exposure in birds attending locust outbreaks, we measured total plasma cholinesterase (ChE), butrylcholinesterase (BChE), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
(43 reference statements)
1
28
1
Order By: Relevance
“…Such a scenario occurs in eastern Australia, where we have previously established that a variety of Australian native birds are exposed to fenitrothion during pesticide application for locust control (Fildes et al 2006). Although the total application of pesticides by the Australian Plague Locust Commission varies from season to season depending on rainfall and other weather conditions, the average annual amount of fenitrothion applied for locust control from 1980 to 1998 was estimated to be 60-80 t year À1 (National Registration Authority 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Such a scenario occurs in eastern Australia, where we have previously established that a variety of Australian native birds are exposed to fenitrothion during pesticide application for locust control (Fildes et al 2006). Although the total application of pesticides by the Australian Plague Locust Commission varies from season to season depending on rainfall and other weather conditions, the average annual amount of fenitrothion applied for locust control from 1980 to 1998 was estimated to be 60-80 t year À1 (National Registration Authority 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example, field studies with birds and reptiles have shown that this diagnostic index of OP toxicity enabled to identify exposed individuals who ChE activity levels were not significantly different from those of non-exposed individuals. [33][34][35] Reactivation of earthworm phosphorylated ChE activity with 2-PAM has revealed as a promising tool for field monitoring of pesticide. 37) However, this attractive methodology requires field validation to be accepted as a suitable indicator of OP exposure, and furthermore, other oximes (e.g., obidoxime, diacetylmonoxime) and esterases (e.g., CbE) should be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Some field studies with birds and reptiles have used the chemical reactivation of phosphorylated ChE activity with oximes as a complementary and specific diagnostic index of OP toxicity. [33][34][35] Generally, the sample tested for ChE inhibition by OPs is incubated with oximes such as pyridine-2-aldoxime methochloride (2-PAM). An increase of ChE activity in the 2-PAM-treated sample compared to the corresponding control (without the oxime) is attributed to the ability of this nucleophilic compound to remove the OP bound to the active site of the esterase.…”
Section: Need For Field Studiesmentioning
confidence: 99%
“…However, this method is hampered in wild birds by autolysis of carcasses, lack of availability of ingesta, insecticide concentrations below detection limits, or exposure through the dermal route rather than ingestion (Shimsoni et al 2012). More recently, the measurement of blood or tissue ChE activity has been used to diagnose OP or carbamate insecticide toxicosis in animals (Fairbrother et al 1991;Fairbrother 1996;Fildes et al 2006Fildes et al , 2009Shimsoni et al 2012). If brain AChE activity is inhibited by 20% from normal, exposure to an anticholinesterase compound is considered likely; however, the accepted diagnostic convention is that whole-brain AChE inhibition .50% is indicative of anti-ChE toxicosis (Ludke et al 1975;Hill and Fleming 1982).…”
Section: Introductionmentioning
confidence: 99%